INFORMAL SEGREGATION ILLUMINATED - Foster, Don (PINS-Psychology in Society, 2025)
Durrheim, Kevin & Dixon, John (2005) Racial encounter: The social psychology of contact and desegregation. London: Routledge. ISBN 978-0415305327. Pages 256. This is a marvellous book. It is sharp, clear, bright-minded and deals with a very important issue for group relations in general: the psychology of segregation and desegregation. It is a major contribution to our new era (post 1990) understanding of contact and group relations in deeply divided societies. While the focus of empirical research is on South Africa the issues under consideration are more widespread, and a good deal of the literature surveyed deals with contact and racial relations in the United States. The book sets out a series of studies on contact and segregation, on vacation time beaches of south coast KwaZulu-Natal. Why is this book so good? I will give a number of reasons.